Characterization of PicoGreen Interaction with dsDNA and the Origin of Its Fluorescence Enhancement upon Binding - Dragan, A.I. (The Biophysical Society, 2010)
PicoGreen is a fluorescent probe that binds dsDNA and forms a highly luminescent complex when compared to the free dye in solution. This unique probe is widely used in DNA quantitation assays but has limited application in biophysical analysis of DNA and DNA-protein systems due to limited knowledge pertaining to its physical properties and characteristics of DNA binding. Here we have investigated PicoGreen binding to DNA to reveal the origin and mode of PicoGreen/DNA interactions, in particular the role of electrostatic and nonelectrostatic interactions in formation of the complex, as well as demonstrating minor groove binding specificity. Analysis of the fluorescence properties of free PicoGreen, the diffusion properties of PG/DNA complexes, and the excited-state lifetime changes upon DNA binding and change in solvent polarity, as well as the viscosity, reveal that quenching of PicoGreen in the free state results from its intramolecular dynamic fluctuations. On binding to DNA, intercalation and electrostatic interactions immobilize the dye molecule, resulting in a >1000-fold enhancement in its fluorescence. Based on the results of this study, a model of PicoGreen/DNA complex formation is proposed.